The osteoimmunology of orthodontic tooth movement: Clinical correlates of inflammatory-mediated crestal bone resorption - Basha, Abdulkarim; Shaheen, Rakan Saifuddin; Almutairi, Abdulaziz Rassam; Almutairi, Abdulaziz Abdulrhman; Alotaibi, Meshal Bader; Alarbid, Abdullah Ahmed (Edelweiss Applied Science and Technology, 2025)
While orthodontic treatment is known to stimulate bone remodeling, its effects on the delicate crestal bone between teeth have raised clinical concerns. To explore this, this study examined records from 556 patients who underwent orthodontic care at Riyadh Elm University, Riyadh, Saudi Arabia. The findings showed measurable bone loss after treatment, with notable differences based on the methods used and the patient’s age. Mini-screws, often employed for anchorage, correlated with the most significant bone reduction, likely from localized trauma and inflammation during placement. In contrast, clear aligners had the gentlest impact, preserving bone levels more effectively. Older patients (35+ years) faced greater bone loss than younger ones (13–18 years), reflecting natural age-related changes in bone density and healing. Interestingly, gender played no detectable role in these outcomes. These insights stress the value of customized treatment plans, especially for older adults or those with existing periodontal issues. Regular monitoring of bone health before, during, and after orthodontics is crucial to minimizing risks. Approaches like gentler force systems and precise mini-screw protocols could help safeguard bone integrity. Close teamwork between orthodontists and periodontists may further optimize results. The study’s retrospective nature and single-center data mean broader conclusions require caution. Future research tracking patients over time could clarify long-term effects, while investigating systemic factors (e.g., osteoporosis) might uncover additional risks. Ultimately, the study underscores a key balance in orthodontics: achieving straighter teeth without compromising the foundation that supports them.